Effect of metoclopramide on gastric function in man - Connell, A. M. (1969)
The effects of metoclopramide on gastric emptying and gastric secretion have been assessed in man using the double sampling test meal. Metoclopramide increases the rate of emptying of the stomach. The magnitude of the effect is directly related to the initial emptying time. Metoclopramide has no effect on the acid response to a water test meal.